Accreditation the Education Development Centers of Medical-Sciences Universities: Another Step toward Quality Improvement in Education - M Mohagheghi; F Shoghi; N Momtazmanesh; AA Haghdoost; MH Mehrolhassani (Tehran University of Medical Sciences, 2013)
Background: : In order to improve the quality of education in universities of medical sciences (UMS), and because of the key role of education development centers (EDCs), an accreditation scheme was developed to evaluate their performance.Method: A group of experts in the medical education field was selected based on pre-defined criteria by EDC of Ministry of Health and Medical education. The team, worked intensively for 6 months to develop a list of essential standards to assess the performance of EDCs. Having checked for the content validity of standards, clear and measurable indicators were created via consensus. Then, required information were collected from UMS EDCs; the first round of accreditation was carried out just to check the acceptability of this scheme, and make force universities to prepare themselves for the next factual round of accreditation.Results: Five standards domains were developed as the conceptual framework for defining main categories of indicators. This included: governing and leadership, educational planning, faculty development, assessment and examination and research in education. Nearly all of UMS filled all required data forms precisely with minimum confusion which shows the practicality of this accreditation scheme.Conclusion: It seems that the UMS have enough interest to provide required information for this accreditation scheme. However, in order to receive promising results, most of universities have to work intensively in order to prepare minimum levels in all required standards. However, it seems that in long term, implementation of a valid accreditation scheme plays an important role in improvement of the quality of medical education around the country.